Odpowiedź :
d)
[tex]3^2\cdot5^6+4^2\cdot5^6=(3^3+4^4)\cdot5^6=(9+16)\cdot5^6=\\\\=25\cdot5^6 = 5^2\cdot5^6=5^{2+6}=\bold{5^8}[/tex]
e)
[tex]5^1\cdot5^6+5^2\cdot5^5+5^3\cdot5^4+5^4\cdot5^3+5^5\cdot5^2=\\\\=5^{1+6}+5^{2+5}+5^{3+4}+5^{4+3}+5^{5+2}=\\\\=5^7+5^7+5^7+5^7+5^7=5\cdot5^7=5^{1+7}=\bold{5^8}[/tex]
f)
[tex]\dfrac{5^2\cdot125}{5^0+24}=\dfrac{5^2\cdot5^3}{1+24}=\dfrac{5^{2+3}}{25}=\dfrac{5^{5}}{5^2}=5^{5-2}=\bold{5^3}[/tex]
[tex]d) \ 3^{2}\cdot5^{6}+4^{2}\cdot5^{6} = 5^{6}(3^{2}+4^{2}) = 5^{6}(9+16) = 5^{6}\cdot25 = 5^{6}\cdot5^{2} = 5^{6+2} = 5^{8}\\\\\\e) \ 5^{1}\cdot5^{6}+5^{2}\cdot5^{5}+5^{3}\cdot5^{4}+5^{4}\cdot5^{3}+5^{5}\cdot5^{2} =5^{1+6}+5^{2+5}+5^{3+4}+5^{4+3}+5^{5+2} =\\\\=5^{7}+5^{7}+5^{7}+5^{7}+5^{7} =5\cdot5^{7} = 5^{1+7} = 5^{8}[/tex]
[tex]f) \ \frac{5^{2}\cdot125}{5^{0}+24}=\frac{5^{2}\cdot5^{3}}{1+24} = \frac{5^{2+3}}{25} = \frac{5^{5}}{5^{2}} = 5^{5-2} = 5^{3}[/tex]
Skorzystano z własności potęgowania:
[tex]a^{m}\cdot a^{n} = a^{m+n}\\\\a^{m}:a^{n} = a^{m-n}\\\\(a^{m})^{n} = a^{m\cdot n}\\\\a^{0} = 1[/tex]